Perancangan Mebel Multifungsi Bermain Motorik untuk Kegunaan Pertumbuhan Balita di Rumah - Catherine Cynthia Kusuma (Intra, 2017)
Gaming is an activity that can be integrated in Early Childhood learning. The world of play is a colorful and fun world. Players will be comforted and happy to do so. From the word "play" alone has shown that this activity has an impact to give the refreshment of mind from the various activities that saturate. For children, playing has a very important role. Some psychologists argue that play activities can be a means for child development. By doing the game, the children will be physically trained. Thus, cognitive and social skills will develop. Character of children who likes to play makes us a designer should pay attention to some things that are about the concept, goals and requirements of the game for children, the classification of children's play activities, materials and game tools in accordance with the development of children, as well as the implementation of the use of games and play equipment in playing activities. The purpose of this writing is that parents still play an important role in terms of supervising the growth of children at home. Having studied in theory, it can be concluded that learning by using the game method is very appropriate with the character of early childhood. Therefore the manufacture of this furniture is made to be in accordance with the motor function of the activity required by the child. With proper management of the game in learning can help the child as an effort in helping the child's development as much as possible.